Pengaruh Masukya Budaya Kota Terhadap Akhlak Remaja Desa Untemanis - Alkhoni Dahni Dalimunte, Parluhutan Siregar , Ismet Sari (Pusdikra Publishing, 2021)
This research was conducted to find out how the morals of the teenagers in Untemanis Village and what influenced the morals of these teenagers. Findings in the field that many teenagers' morals do not reflect good morals as recommended by religion. Based on the available data, the morals of this village youth are much involved and influenced by the culture of teenagers in urban areas, such as speaking style, lifestyle and behavior. The results of this study describe how the connection between urban culture and the Untemanis village community, how the moral shift of the Untemanis village youth after the entry of culture from the city and parents' views on the moral shift of the adolescents. From the data found in the field that the shift in morals that occurred such as language and speech, association, manners and religious conditions of teenagers in Untemanis village